2014
DOI: 10.21466/ac.piccclc.2014
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheter causing life‐threatening cardiac tamponade

Abstract: We report a 60-yr-old female who had a peripherally inserted central catheter (PICC) for parenteral nutrition (TPN). Insertion was uneventful although the line was seen to extend into the right ventricle. The line was re-positioned but soon after commencing TPN she collapsed. Computerised tomography pulmonary angiography (CTPA) demonstrated a pericardial effusion with a high fat content. Pericardiocentesis revealed fluid with a high triglyceride content and confirmed pericardial placement of ther tip of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has also been reported that in addition to catheter displacement, other factors, such as the material, length, and size of the catheter, duration of parenteral nutrition, osmolarity, and composition of the infused fluids may severely affect and worsen complications and outcomes related to cardiac tamponade. For example, it was reported in one study that pericardial presence of high-potassium infused fluid resulted in electrocardiogram alterations showing a pattern of hyperkalemia instead of a pattern of cardiac tamponade [1, 9,12]. Another study also showed that tamponade was frequently observed in cases with PICC inserted through aperipheral vein compared to a central vein [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that in addition to catheter displacement, other factors, such as the material, length, and size of the catheter, duration of parenteral nutrition, osmolarity, and composition of the infused fluids may severely affect and worsen complications and outcomes related to cardiac tamponade. For example, it was reported in one study that pericardial presence of high-potassium infused fluid resulted in electrocardiogram alterations showing a pattern of hyperkalemia instead of a pattern of cardiac tamponade [1, 9,12]. Another study also showed that tamponade was frequently observed in cases with PICC inserted through aperipheral vein compared to a central vein [4].…”
Section: Discussionmentioning
confidence: 99%
“…Of the above complications, tamponade is a rare but fatal condition that occurs following catheter dislocation and pericardial perforation [8]. Cardiac tamponade is responsible for 47-100% of the mortality rate [9].…”
Section: Introductionmentioning
confidence: 99%